Gene expression profiles of novel caprine placental prolactin-related proteins similar to bovine placental prolactin-related proteins - Ushizawa, Koichi (BioMed Central, 2007)
BACKGROUND: This study reports the identification of a full-length cDNA sequence for two novel caprine prolactin-related proteins (cPRP1 and cPRP6), and their localization and quantitative expression in the placenta. Caprine PRPs are compared with known bovine PRPs. We examined their evolution and role in the ruminant placenta. RESULTS: Full-length cPRP1 and cPRP6 cDNA were cloned with a 717- and 720- nucleotide open-reading frame corresponding to proteins of 238 and 239 amino acids. The cPRP1 predicted amino acid sequence shares a 72% homology with bovine PRP1 (bPRP1). The cPRP6 predicted amino acid sequence shares a 74% homology with bovine PRP6 (bPRP6). The two cPRPs as well as bPRPs were detected only in the placentome by RT-PCR. Analysis by in situ hybridization revealed the presence of both cPRPs mRNA in the trophoblast binucleate cells. These mRNA were quantified by real-time RT-PCR analysis of the placentome at 30, 50, 90 and 140 days of pregnancy. Both new cPRP genes were able to translate a mature protein in a mammalian cell-expression system. Western blotting established the molecular sizes of 33 kDa for cPRP1 with FLAG-tag and 45 kDa for cPRP6 with FLAG-tag. The sequence properties and localized expression of cPRP1 and cPRP6 were similar to those of bovine. However, their expression profiles differed from those in bovine placenta. Although this study demonstrated possible roles of PRPs in caprine placenta, PRPs may regulate binucleate-cell functions like those in bovine, but their crucial roles are still unclear. CONCLUSION: We have identified the novel PRPs in caprine placenta. Localization and quantitative expression of caprine PRPs were compared with bovine PRPs. The data indicate that PRP genes in caprine placenta have coordination functions for gestation, as they do in bovine. This is the first study of PRPs function in caprine placenta.